2019
DOI: 10.1186/s12885-019-6318-5
|View full text |Cite
|
Sign up to set email alerts
|

Frozen section accurately allows pathological characterization of endometrial cancer in patients with a preoperative ambiguous or inconclusive diagnoses: our experience

Abstract: BackgroundThe aim of this study was to assess the agreement rate between intraoperative evaluation (IOE) and final diagnosis (FD) in a series of surgically resected endometrial carcinoma (EC), with a preoperative ambiguous or inconclusive diagnosis by endometrial biopsies and imaging.MethodsA retrospective study was performed selecting patients who underwent surgery with IOE for suspected EC at our institution from 2012 to 2018. A K coefficient was determined with respect to the histotype, tumor grade, myometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 27 publications
(25 reference statements)
2
24
0
Order By: Relevance
“…The analysis showed that in all groups pre-operative biopsy had a good correspondence with final histology and grade and FS was superimposable to final histology for both parameters ( Table 4 ). This correspondence is conserved also in LS patients even if literature reports evidences about the heterogeneity of EC and this may lead to a greater difficulty in histopathological diagnosis, especially in pre-operative biopsies [ 45 , 46 ]. Our data implies the possibility to correctly assess pre-operative/intra-operative risk also in LS group.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis showed that in all groups pre-operative biopsy had a good correspondence with final histology and grade and FS was superimposable to final histology for both parameters ( Table 4 ). This correspondence is conserved also in LS patients even if literature reports evidences about the heterogeneity of EC and this may lead to a greater difficulty in histopathological diagnosis, especially in pre-operative biopsies [ 45 , 46 ]. Our data implies the possibility to correctly assess pre-operative/intra-operative risk also in LS group.…”
Section: Discussionmentioning
confidence: 99%
“…There is frequently an overlap between histologic subtypes and grade determination complicating clinical decision making. Therefore, interobserver diagnostic agreement is still suboptimal, particularly among the high-grade histotypes and in frozen section specimens [ 10 , 11 ]. In 2013, The Cancer Genome Atlas (TCGA) Research Network reported a large scale, integrated genomic, transcriptomic, and proteomic analysis of 373 endometrial carcinomas, including 307 EECs, 53 SECs, and 13 mixed cases.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in young women who wish to preserve their fertility, a diagnosis of high-grade carcinoma on biopsy specimen precludes the possibility of a conservative management [15]. In the intraoperative assessment of frozen sections, a misdiagnosis of high-grade carcinoma may lead to unnecessary lymphadenectomy with related complications [16]. In the case of FIGO stage I on the final hysterectomy specimen, such pitfall may lead to unnecessary adjuvant treatment [15].…”
Section: Discussionmentioning
confidence: 99%